Development of ESD-criteria for Visualization and Evaluation of Implementation Processes in (Environmental) Education Concepts - Wittlich, Christian; Brühne, Thomas (Journal of Geography Education, 2020)
For some years now, ESD certification procedures have been taking place in pedagogical educational institutions, following the call to implement ESD more structurally in the educational system (e.g. Sustainable University, ESD learning places). In this context, the lack of a universal definition of ESD proves to be problematic. This publication presents a theory-based research approach that uses a search of ESD documents to identify commonalities in content. In order to come closer to the goal of categorical theoretical condensation, particularly relevant text passages were qualitatively recorded, and coding processes were carried out. As a result, sixteen ESD criteria were generated, which can be used as a kind of reference system in order to make implementation processes of ESD more visible, especially in out-of-school places of learning.
Keywords: ESD-Criteria, Evaluation, Sustainability, Extracurricular learning venues